Muhammad Abduh's Perspective on Polygamy in the Indonesian Social Context - Husnah, Nurul; Fauzi, Ahmad; Arafah, Siti (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2024)
This article aims to delve into Muhammad Abduh's views on polygamy, evaluate its relevance in the social context of Indonesian society, and offer a broader understanding and potential solutions for Indonesian society to perceive the practice of polygamy. The research method employed is a qualitative approach focusing on literature review. This approach is designed to comprehend and analyze Muhammad Abduh's perspectives and thoughts regarding the practice of polygamy, especially within the Islamic teachings and its impact on social dynamics in Indonesia. The research findings indicate that Muhammad Abduh consistently displayed a critical stance towards polygamy. He consistently highlighted the importance of justice, equality, and well-being for all parties involved in such contexts. The relevance of Muhammad Abduh's thoughts in the Indonesian context, which encompasses a diverse society, lies in the urgency of recognizing the values of humanity and justice in applying Islamic teachings, particularly in sensitive issues like polygamy. Essentially, Abduh's viewpoints offer a perspective that considers the welfare and protection of individual rights in interpreting Islamic teachings, aligning with the social diversity present in Indonesia. Amir and Rahma argue that Tasir Al-manar has a significant and enduring influence on the formation and development of modern Islam in Indonesia.